Modern radar systems - Meikle, Hamish (Artech House, 2008)
This revised and updated edition to the popular Artech House book, Modern Radar Systems, offers complete and current coverage of the subject, including new material on accuracy, resolution, and convolution and correlation. The book features more than 540 illustrations (drawn in Maple V) that offer a greater understanding of various waveforms, and other two- and three-dimensional functions, to help you more accurately analyze radar system performance. The effects of pulse shaping on transmitter stability and spectra are discussed? a topic which is becoming more and more important in the age of electromagnetic compatibility. The book addresses the importance of low attenuation and reflection between the main radio frequency blocks, including the use of oversized waveguides for long runs. Publisher abstract.
Keywords: Radar.; elektronické knihy; electronic books